A learning process for early childhood: a case of geometry and numbers. (October 2020) - Efriani, A; Zulkardi, Z; Putri, R I I; Aisyah, N
Abstract: The teacher is a parent for young children in school. In maximizing learning in schools, the role of a teacher is needed. This study aims to describe the learning process for childhood by teachers both in plannng, implementatuon, and evaluaton of geometry and numbers. The subjects of this study were 30 teachers from 20 schools in South Sumatra. The method used is descriptive with qualitative and quantitative types. Data were collected using questionnaires and interviews. The results obtained that the implementation of learning undertaken by teachers both in planning, implementation, and evaluation has been carried out in each school. It's just that the implementation is not optimal. It is because there is no awareness of the teacher about the need for learning tools, learning is still not following the stages of development due to the limitations of the media and the lack of teacher creativity. It requires training as an evaluation of the activities that have been carried out.